ANALYSIS OF CONSUMER LENDING PRACTICE IN THE REPUBLIC OF DAGESTAN - M. Madina; N. Magomedova (Вестник Северо-Кавказского федерального университета)
The purpose of this work is to study the types and forms of consumer lending in the Republic of Dagestan and identify its main trends. The current situation in the sphere of consumption of the most important goods and services by the population is analyzed, the role of consumer credit in the activation of demand is determined. The market of bank loans, the conditions for their provision were studied, the main features of the consumer lending sector, as well as the problems of its functioning, were revealed. Based on the analysis of the structure of credit operations carried out in the republic, a conclusion was made about the leading role and positive dynamics of consumer loans in the general line of banking products. Certain measures are proposed to further develop this sector.